1977
DOI: 10.4315/0362-028x-40.11.778
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Aspergillus flavus Strains in Growth and Aflatoxin B1 Production in Relation to Water Activity and Temperature

Abstract: The optimum and limiting conditions of water activity (aw) and temperature for growth of and aflatoxin B1 production by various Aspergillus flavus strains were determined. Agar media were used in which the aw was adjusted by addition of sucrose or glycerine. Optimum temperatures for aflatoxin B1 production at high aw varied with the strain tested being 13–16, 16–24, or 31 C. Strains with a low temperature optimum for aflatoxin B1 production showed fast growth at 37 C without aflatoxin B1 production. A reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…Maximum aflatoxin production was found at 30°C for one strain each of A. fl avus and A. parasiticus (Ogundero 1987). Under high water activity, the optimum temperature for afl atoxin production for three strains of A. fl avus varied from 13° to 31°C depending on the strain (Northolt et al 1977). Schindler et al (1967), using two strains of what would now be called A. parasiticus, found that for one strain afl atoxin B 1 production was highest at 24°C, with much lower afl atoxin levels at 29°C, but for the other strain production at 29°C was only slightly lower than at 24°C.…”
Section: Temperaturementioning
confidence: 95%
“…Maximum aflatoxin production was found at 30°C for one strain each of A. fl avus and A. parasiticus (Ogundero 1987). Under high water activity, the optimum temperature for afl atoxin production for three strains of A. fl avus varied from 13° to 31°C depending on the strain (Northolt et al 1977). Schindler et al (1967), using two strains of what would now be called A. parasiticus, found that for one strain afl atoxin B 1 production was highest at 24°C, with much lower afl atoxin levels at 29°C, but for the other strain production at 29°C was only slightly lower than at 24°C.…”
Section: Temperaturementioning
confidence: 95%
“…A. flavus grows over a wide range of temperature (T; 12e43 C) (Ayerst 1969;Northolt et al 1977;Holmquist et al 1983) with 25e28 C considered optimum for aflatoxin production (Northolt et al 1977;Giorni et al 2007Giorni et al , 2011. Water activity (a w ) also has a significant impact on this fungus, which is able to grow and synthesize AFs down to conditions of 0.73e0.78 and 0.83e0.85 a w respectively (Ayerst 1969;Sanchis & Magan 2004;Giorni et al 2007Giorni et al , 2011.…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, the A parasiticus isolate used in the present study showed an ability to grow and produce concentrations of a¯a-toxins at 15°C higher than reported for A¯avus. Northolt et al 29 pointed out that even differences in fungal strains of A¯avus might explain the different optimum temperatures for toxin production reported by different investigators.…”
Section: 26±28mentioning
confidence: 99%
“…Previously, the optimum temperature for a¯atoxin production by A¯avus was found to be 24±31°C at 0.95±0.99 a w . 29 The temperature limit was between 10 and 13°C and the a w limit for toxin production was between 0.83 and 0.87. Similarly, on maize a temperature of 15±16°C was generally too low for a¯a-toxin production by strains of A¯avus, 7,30,31 although the fungus was able to grow at this temperature at a w values as low as 0.80.…”
Section: 26±28mentioning
confidence: 99%